Answer:
f(x) = (x + 1)³ - (x + 1)² = x³ + 2 x² + x
Step-by-step explanation:
To shift g(x) to the left by one unit, replace all x in the expression of g(x) with (x + 1). How does this work? For example, g(x) = -2 for x = -1 in this question. f(x) = g(x + 1) may also equate -2, but only one unit to the left of x = -1 at x = -2 since -2 + 1 = -1. So is the case for the rest of the points on g(x). f(x) = g(x + 1) leads to the same set of values but only at one unit to the left. Adding one to the independent variable of g(x) shifts the graph to the left by one unit.
To find g(x + 1), replace every x in the equation x³ - x² with (x + 1):
f(x) = g(x + 1) = (x + 1)³ - (x + 1)².
Expand (x + 1)³ - (x + 1)² using the binomial theorem:
f(x) = (x + 1)³ - (x + 1)² = x³ + 3 x² + 3 x + 1 - (x² + 2 x + 1) = x³ + 2 x² + x
Answer:
f (x) = (x-1)^3 - (x-1)^2
Step-by-step explanation:
4(a + 3) = 18 – 2(3 – 2a)
–3
–1
all real numbers
no solution
Question 9
Kersha has two jobs. During the day she works as an office clerk, and in the evening she works as a cashier. Her office job pays her $12.00 per hour. Her cashier job pays her $8.25 per hour. In one week, Kersha worked 55 hours. She earned a total of $585.
How many hours did Kersha work in each job?
Office clerk: 35 hours; cashier: 20 hours
Office clerk: 20 hours; cashier: 35 hours
Office clerk: 31 hours; cashier: 24 hours
Office clerk: 28 hours; cashier: 27 hours